EMPOWERING COMMUNITIES: ASSESSING THE EFFECTIVENESS OF PROGRAMS AND LISTENERSHIP OF COMMUNITY RADIO - Rastogi, Shivam; Suryavanshi, Ravi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Community radio has long been recognized as a powerful tool for empowering marginalized communities by providing them with a platform to voice their concerns, share their stories, and access essential information. Community radio (CR) is a third-tier media, together with broadcasting on public and privately owned radio. This research paper throws light on the listenership pattern of listeners of community radio, their program preferences and CR programs' effectiveness on listeners. A survey was conducted among listeners of ‘Radio Varsha’ which is situated in the Gopalganj district of Bihar for the purpose of data collection and analysis. This study employs a mixed-method approach, combining quantitative survey data and extracts of discussions held with stakeholders and listeners. The research discovered that programs are effective in generating awareness on various topics among listeners. The broadcast content in local languages and dialects was liked by the listeners, thus, leading to the effectiveness of the programs.